Ocena przydatnosci testu RAST w monitorowaniu wydolnosci beztlenowej - Adamczyk, J. G. (Polish Journal of Sport and Tourism, 2011)
Introduction. In athletic high-speed-forced competitions one of basic monitored parameters of the preparation is the level of the anaerobic capacity. The aim of the work was the qualification of the usefulness of the RAST (Running-based Anaerobic Sprint Test) in the estimation of the anaerobic capacity of athletes of sprint athletic competitions. Material and methods. 37 athletes (12 Female and 25 Male) specializing in sprint racing (100 m, 100 m hurdles, 110 m hurdles, 200 m) and the prolonged sprint (400 m and 400 m hurdles) partook in the research. The anaerobic capacity was evaluated by means of the RAST test and the Wingate test. Results. In the RAST test competitors obtained significantly higher values of the maximum power (p<0.001) and the average power (p<0.001), with relation to the Wingate test. Among women such dependences were not ascertained. The fundamentally lower (p<0.001) fatigue index in the RAST test characterized in turn both groups, which can testify about the better adaptation to the run effort. For both tests one ascertained significant dependence between the average power and the maximum power. Moreover, the significant dependence between the fatigue index (FI) and the average and maximum power in the Wingate test was shown. For the RAST test such dependence appeared among FI, and the maximum power. Conclusions. The RAST test gave statistically comparable results only in the case of the average and maximum power among women. The smaller physical load for competitors and decidedly easier organization of the research causes that the RAST test can be used for regular monitoring of the anaerobic capacity level of competitors of athletic run competitions.